Slovak Country Report - Bárány, Eduard; Brhlíková, Radoslava; Colotka, Peter (2000)
The Slovak Republic belongs to a multifarious realm of states where written constitutions make provisions for referenda. Even before the adoption of the Constitution of the Slovak Republic in 1992, Slovakia had some legal provisions enabling local referenda. Thus one may point to the law No. 369 on municipal constitution from the 6th of September 1990. This law made a very first introduction of «referendum» into the Slovak legal system: According to the statement of the § 3.2b) an inhabitant of the municipality has the right to vote in «local referendum». In this way the institution of referendum» started to serve especially for the purpose of obligatory «popular vote» solution of some previously merely administratively solved questions, namely: merger, split and dissolution of a municipality and establishing/canceling official rates.